A Gastronomic Approach to Industrial Aquaculture Waste Utilization - Suat Dikel; Çiğdem Dikel (Turkish Journal of Agriculture: Food Science and Technology)
Aquaculture, while offering significant contributions to global food security, generates substantial amounts of industrial waste, posing environmental and economic challenges. However, this waste also presents untapped potential for innovation in gastronomy. This paper explores the emerging trend of utilizing aquaculture industrial wastes in culinary practices, aiming to reduce waste, promote sustainability, and create novel gastronomic experiences. Through a review of literature and case studies, we examine various methods for repurposing aquaculture waste, including upcycling into new food products, incorporation into culinary dishes, and extraction of valuable components. Additionally, we highlight successful initiatives that have integrated aquaculture waste into gastronomy, emphasizing the benefits of waste reduction, sustainable food practices, and culinary innovation. Challenges such as food safety, taste, and consumer acceptance are acknowledged, with strategies proposed for addressing these issues. Finally, we discuss future directions for research and development in this field, identifying opportunities for collaboration between the aquaculture industry and the gastronomy sector. By exploring the utilization of aquaculture industrial wastes in gastronomy, this paper contributes to a deeper understanding of sustainable food practices and culinary creativity in the context of aquaculture waste management.